Expert on impact of the coronavirus pandemic on the event industry, big-business football, and the small sport clubs - Kurscheidt, M. (Universität Bayreuth, 2020)
The consequences of the lockdown for large and small sport clubs, for companies and freelancers in the event business will be serious. "Only when something is going on, will money be earned", says Prof. Dr. Markus Kurscheidt, Chair of Sport Science II - Sport Governance and Event Management at the University of Bayreuth. He sees big problems ahead for amateur competitive sports: He fears that many regional clubs will not survive the crisis. Moreover, according to Kurscheidt, the recovery after the end of the initial restrictions will not be enough for the event industry: "To compensate for the losses, we would have to declare Wednesday a day off until the end of the year."